Chi's sweet adventures. 2 - Natsume, Kinoko; Konami, Kanata, 1958- (Vertial Comics, 2018)
Includes a collection of comics featuring a kitten named Chi and his family and friends. Here Chi freezes during a power outage, goes to the vet, exercises with mom, takes shelter from the rain, and plays with his friends.